Heterogeneous impact of environmental taxes on environmental quality: Tax domain based evidence from the nordic countries by nonparametric quantile approaches - Depren, Ozer; Kartal, Mustafa Tevfik; Ayhan, Fatih; Depren, Serpil Kilic (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2023)
This study aims to examine the heterogeneous causality and impact of environmental taxes at both aggregated and disaggregated levels on environmental quality. In this context, the study focuses on Nordic countries as green economies; handles carbon dioxide (CO2) emissions as an environmental quality indicator; includes aggregated and disaggregated levels of environmental taxes as explanatory variables; uses quarterly data for the period 1994/Q1-2020/Q4 as the most recent available data; applies novel nonparametric Granger causality-in-quantiles (GCQ) and quantile-on-quantile regression (QQR) approaches as the main models while using quantile regression (QR) for robustness check. The results present that (i) causal impacts of environmental taxes on CO2 emissions exist in most quantiles at disaggregated levels excluding some lower, middle, and higher quantiles, whereas indicator-, country-, and quantile-based results vary; (ii) environmental tax on energy (ETE) has a mainly decreasing impact in Iceland, a mixed impact in Denmark, Finland, Norway, and Sweden based on quantiles; (iii) environmental tax on pollution (ETP) has the highest decreasing impact in most quantiles in Denmark, Iceland, and Norway; (iv) environmental tax in transport (ETT) has a decreasing impact in Norway and Sweden, whereas it has a reverse impact in Denmark, Finland, and Iceland; (v) impact of total environmental tax (TET) has a decreasing impact in Denmark and Norway at some quantiles, whereas an increasing impact in Finland, Iceland, and Sweden; (vi) the robustness of the QQR results are confirmed by the QR approach. Hence, the results un-derline the importance of country and quantile-based disaggregated analyses and Nordic countries should re-adjust environmental taxes to increase environmental quality.
Keywords: Environmental tax; Environmental quality; Environmental Nordic countries; GCQ; QQR; CO2 EMISSIONS; RENEWABLE ENERGY; CARBON EMISSIONS; ECONOMIC-GROWTH; Environmental Sciences & Ecology